Antioxidants in Age-Related Diseases and Anti-Aging Strategies - Marius Emil Rusu; Ionel Fizeșan; Laurian Vlase; Daniela-Saveta Popa (MDPI AG, 2022)
Aging is an intricate process and an important risk factor in the development and advancement of many disorders [...]